(untitled) (Reflection and Critique Law Magazine, 2022)
Contemporary democratic society is faced with a paradox, because, in the same historical moment in which it created a public sphere, open to the participation of all, and whose scope and influence were previously unknown, it witnesses a deterioration of this sphere by an improper use of ways communication and expression, leading to a threat to democracy. Representative democracy is thus weakened, raising the need for a participatory and deliberative democracy, which requires a solid, responsible and active public sphere. This work aims to examine the constitution and structural change of the public sphere, in the light of the thinking of Jürgen Habermas. A bibliographic research was adopted to try to answer the problem if the Habermasian conception of the public sphere allows us to glimpse the emancipatory potential of communicative action, rooted in the unaffordable assumptions of human communication, which takes place in this public sphere and which points to a responsible and rational exercise citizenship, a condition of democratic rule.